Studi hubungan antara penguasaan diksi dan kemampuan berpikir logis dengan keterampilan menulis hasil wawancara peserta didik kelas IV SD - Estiningtyas, Ayu; Slamet, STY; Budiharto, Tri (Didaktika Dwija Indria, 2021)
Language skills that must be possessed by all students in schools include basic aspects, one of which is writing. The important thing when learning to write is mastering proper diction and logical thinking. There are problems that occur in the education system and schools throughout Indonesia in terms of writing skills, where teaching Indonesian is still monopolized by the knowledge aspect. Students learn language theory rather than language techniques so that the ability to compile a written work such as a report is inadequate. This research was conducted on fourth grade students of the Tambak District Elementary School in the academic year 2020/2021 with a sample size of 120 students. The whole data collection in this study used the test method to obtain test data from the writing skills of interview reports and data on students' diction and logical thinking. This study uses quantitative methods and the analysis technique used is normality test and hypothesis testing with regression analysis. The results of this study indicate that mastering proper diction and logical thinking has a positive and significant effect on the variable of skills in writing interview reports, either partially or simultaneously.